The Role of Dua Lipa as a Cultural Diplomacy Agent in Promoting Kosovo’s Nation Branding in Europe - Pambagyo, Wahyu Dwi (Department of Political Science, Faculty of Social and Political Science, Udayana University, 2025)
The use of soft power through global celebrities allows countries to leverage the influence of famous figures to introduce themselves to the international community, as Dua Lipa did in promoting Kosovo to the international community. This study aims to describe Dua Lipa's role as a cultural diplomacy agent in Kosovo's nation branding efforts on the international stage. Using celebrity diplomacy theory, the study examines how Dua Lipa, as one of the global music icons, leverages her international influence to promote a positive image of Kosovo. A qualitative descriptive approach with literature review was used, collecting sources from books, journals, and mainstream media. The findings reveal that Dua Lipa's involvement in initiatives such as the Sunny Hill Festival has significantly contributed to shaping Kosovo's global nation branding, attracting international tourists, and influencing policy changes such as the liberalization of Kosovo's visa policy for visits to European countries.